Writing Alone or Together: Police Officers’ Collaborative Reports of an Incident - Vredeveldt, Annelies (Criminal justice and behavior, 2018)
After witnessing an incident, police officers may write their report collaboratively. We examined how collaboration influences the amount and accuracy of information in police reports. Eighty-six police officers participated, in pairs, in a live training scenario. Officers wrote a report about the incident, either with their partner or individually. Reports by two officers working together (collaborative performance) contained less information than reports by two officers working individually (nominal performance), with no difference in accuracy. After the first report, officers who had worked individually wrote a collaborative report. Police officers who recorded their own memories prior to collaboration included less incorrect information in the collaborative report than police officers who wrote a collaborative report immediately after the incident. Finally, content-focused retrieval strategies (acknowledge, repeat, rephrase, elaborate) during the officers’ discussion positively predicted the amount of information in collaborative reports. Practical recommendations for the police and suggestions for further research are provided.